Digitalisasi Pengelolaan Keuangan Usaha Bagi Wirausaha Muda di SMA Negeri 1 Petang - I Gst. Agung Pramesti Dwi Putri; A.A. Gede Adi Mega Putra; A. A. Istri Ita Paramitha; I Nyoman Yudi Anggara Wijaya (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Building an entrepreneurial spirit is one of the goals intended to be achieved in high school education. This entrepreneurial spirit is essential for creating students who are productive, creative, and innovative. One of the skills that must be mastered by young entrepreneurs is business financial management. Digitalization in financial management can be a solution to improve efficiency and transparency in business financial management. Therefore, it is important for students at SMAN 1 Petang to complement their entrepreneurship knowledge with business financial management skills. This community service aims to equip young entrepreneurs at SMAN 1 Petang with financial management skills by utilizing the latest technology. The community service activity was conducted in April 2024, involving 37 students who are members of the entrepreneurship extracurricular activity. The outcome of this community service is that young entrepreneurs have gained an understanding of product cost calculation and financial recording and management using the BukuWarung. With the financial management skills acquired, young entrepreneurs will be better equipped to manage and develop their businesses